2013
DOI: 10.1080/10543406.2013.736810
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood Ratio Test-Based Method for Signal Detection in Drug Classes Using FDA's AERS Database

Abstract: In 1968 the Food and Drug Administration (FDA) established the Adverse Event Reporting System (AERS) database containing data on adverse events (AEs) reported by patients, health care providers, and other sources through a spontaneous reporting system. FDA uses AERS for monitoring the safety of the drugs on the market after approval. Most statistical methods that are available in the literature to analyze large postmarket drug safety data for identifying drug-event combinations with disproportionately high fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 11 publications
0
45
0
Order By: Relevance
“…That is, “The EudraVigilance Expert Working Group noted that thresholds commonly used to detect signals in spontaneous data are a trade‐off between two conflicting goals: either generating too many false positive signals if the threshold is too low or missing true signals if this threshold is too high. Given this trade‐off, it is important to identify and calibrate methods to strike a reasonable balance between these two parameters.” Although this evaluation was very extensive, it did not include a more recently developed approach using a likelihood ratio test (LRT)‐based method and the FDR‐based extensions of the aforementioned methods. In addition, comparisons among these methods are based on using data from different databases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, “The EudraVigilance Expert Working Group noted that thresholds commonly used to detect signals in spontaneous data are a trade‐off between two conflicting goals: either generating too many false positive signals if the threshold is too low or missing true signals if this threshold is too high. Given this trade‐off, it is important to identify and calibrate methods to strike a reasonable balance between these two parameters.” Although this evaluation was very extensive, it did not include a more recently developed approach using a likelihood ratio test (LRT)‐based method and the FDR‐based extensions of the aforementioned methods. In addition, comparisons among these methods are based on using data from different databases.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to these outcome measures as the AE‐based and drug‐based outcome measures, respectively. In their evaluation of the LRT method, Huang et al used the AE‐based method but demonstrated good performance in several contexts . Specifically, the LRT method controls both the type I error and the FDR well while retaining good power and sensitivity, and Huang et al compared its performance with the PRR and BCPNN methods.…”
Section: Introductionmentioning
confidence: 99%
“…By treating a drug combination as a new drug, the disproportionality measurements can be obtained, accordingly. For instance, Huang et al . introduced an extended LRT method that can be used for detecting signals for multiple drugs (or ADEs) in a drug class (or in an ADE group).…”
Section: Ddi Data Mining Methods Using the Postmarketing Surveillancementioning
confidence: 99%
“…Applying the latter methods to a reference set of adverse events with 220 drugs in four pharmaceutical companies, one national and two international safety databases, they concluded: 'The choice of disproportionality statistic does not appreciably affect the achievable range of SD performance and so this can be primarily based on ease of implementation, interpretation and minimization of computing resources'. Even with new varieties of DA, such as p-plots, Ƴ-multinomial modeling and likelihood-based methods [Johnson et al 2012;Huang et al 2013;, the latest data do not support a religious devotion to a single method.…”
Section: Discussionmentioning
confidence: 99%